2021
DOI: 10.1371/journal.pone.0251602
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Abbott RealTime MTB and RIF/INH resistance assays for the detection of Mycobacterium Tuberculosis and resistance markers in sputum specimens

Abstract: Background The Abbott RealTime MTB is an assay for the detection of Mycobacterium tuberculosis (MTB) complex DNA from respiratory specimens in combination with the Abbott RealTime RIF/INH assay for the detection of genetic resistance markers for isoniazid (INH) and rifampicin (RIF) from MTB positive isolates. Hence, this study aimed to evaluate the performance of the Abbott RealTime MTB and RIF/INH assays. Methods A cross-sectional study was conducted on 289 study subjects presumptive to have pulmonary tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
3
4
0
1
Order By: Relevance
“…6 The sensitivity and specificity of the Abbott RealTime MTB and INH/RIF assays for detection of Mtb and detection of INH resistance were 92.4% (95% CI 83.6-96.9) and 95.4% (95% CI 91.1-97.7) and 84.2% (95% CI 60.4-96.6) and 100% (95% CI 89.7-100), respectively. In the case of RIF resistance, no discrepant results were observed, 73 a finding supported by several other studies. [74][75][76][77] The multiplexed real-time PCR (MAX MDR-TB) (Becton Dickinson) NAAT platform using five-colour detection enables direct detection of Mtb in raw sputum or concentrated sputum sediments.…”
Section: Moderate Complexity Automated Naatssupporting
confidence: 86%
“…6 The sensitivity and specificity of the Abbott RealTime MTB and INH/RIF assays for detection of Mtb and detection of INH resistance were 92.4% (95% CI 83.6-96.9) and 95.4% (95% CI 91.1-97.7) and 84.2% (95% CI 60.4-96.6) and 100% (95% CI 89.7-100), respectively. In the case of RIF resistance, no discrepant results were observed, 73 a finding supported by several other studies. [74][75][76][77] The multiplexed real-time PCR (MAX MDR-TB) (Becton Dickinson) NAAT platform using five-colour detection enables direct detection of Mtb in raw sputum or concentrated sputum sediments.…”
Section: Moderate Complexity Automated Naatssupporting
confidence: 86%
“…Despite this wide range of performance, our study demonstrated that the overall sensitivity and specificity of the Indigen MTB/DR-TB RT-PCR assay to detect MTB in sputum were 94.1 and 98.1%, respectively, in comparison to the standard TB culture method, along with a kappa value of ≥0.9. Concordant with our results, studies on the performance of a commercial IS6110 sequence-based PCR assay, Abbot Real-Time RIF/INH, reported a sensitivity level of 92.4% (Araya et al, 2021), while another metaanalysis study confirmed that the assay had sensitivity and specificity levels of 96 and 97%, respectively (Wang et al, 2019). Moreover, another comparison study between the IS6110-Taq Man-based PCR assay and GeneXpert RIF/INH reported that IS6110-Taq Man-based had better sensitivity (84% vs. 79%, respectively, 19).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, another comparison study between the IS6110-Taq Man-based PCR assay and GeneXpert RIF/INH reported that IS6110-Taq Man-based had better sensitivity (84% vs. 79%, respectively, 19). All these findings support that multicopy target IS6110, which is present at 10 to 15 copies in most genomes of MTB, contributes to the better sensitivity of the TB PCR-based assay (Eisenach et al, 1990;Araya et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Los cultivos utilizados en nuestra institución son realizados por medio sólido Ogawa Kuddo; la prueba molecular se realizó mediante el ensayo Abbott RealTime MTB RIF/ INH Resistance m2000 ® . El ensayo Abbott RealTime MTB RIF/INH Resistance m2000 ® , permite la determinación de M. tuberculosis a partir de la secuencia de inserción 6110 (IS6110) y el antígeno proteínico b (PAB) en muestras de esputo o lavado bronco alveolar, con un límite de detección de 60 UFC/ml, adicionalmente permite la detección cualitativa de resistencia a rifampicina e isoniazida (7).…”
Section: Métodosunclassified